Establishing Multifunctional Interface Layer of Perovskite Ligand Modified Lead Sulfide Quantum Dots for Improving the Performance and Stability of Perovskite Solar Cells. Issue 41 (22nd September 2020) - Ma, Ruiman; Ren, Zhenwei; Li, Can; Wang, Yong; Huang, Zhanfeng; Zhao, Yong; Yang, Tingbin; Liang, Yongye; Sun, Xiao Wei; Choy, Wallace C. H.
Abstract: While organic–inorganic halide perovskite solar cells (PSCs) show great potential for realizing low‐cost and easily fabricated photovoltaics, the unexpected defects and long‐term stability against moisture are the main issues hindering their practical applications. Herein, a strategy is demonstrated to address the main issues by introducing lead sulfide quantum dots (QDs) on the perovskite surface as the multifunctional interface layer on perovskite film through establishing perovskite as the ligand on PbS QDs. Meanwhile, the multifunctions are featured in three aspects including the strong interactions of PbS QDs with perovskites particularly at the grain boundaries favoring good QDs coverage on perovskites for ultimate smooth morphology; an inhibition of iodide ions mobilization by the strong interaction between iodide and the incorporated QDs; and the reduction of the dangling bonds of Pb 2+ by the sulfur atoms of PbS QDs. Finally, the device performances are highly improved due to the reduced defects and non‐radiative recombination. The results show that both open‐circuit voltage and fill factor are significantly improved to the high values of 1.13 V and 80%, respectively in CH3 NH3 PbI3 ‐based PSCs, offering a high efficiency of 20.64%. The QDs incorporation also enhances PSCs' stability benefitting from the induced hydrophobic surface and suppressed iodide mobilization. Abstract : A multifunctional interface layer is formed on perovskite film through establishing perovskite as the ligand on PbS quantum dots (QDs). The multifunctions are strong interactions of PbS QDs with perovskites particularly at the grain boundaries, an inhibition of iodide ions mobilization, and the reduction of the dangling bonds of Pb 2+ . Finally, the perovskite device efficiency and stability are highly improved.